A feasibility study of dementia communication training based on the VERA framework for pre-registration nurses: Part II impact on student experience. (April 2018) - Naughton, Corina; Beard, Chloe; Tzouvara, Vasiliki; Pegram, Anne; Verity, Rebecca; Eley, Rhiannon; Hingley, David
Abstract: Background: People living with dementia have complex communication needs, especially during acute hospital admissions. The VERA framework (validation, emotion, reassurance, activity) was designed to promote person centred communication between student nurses and people living with dementia, but there is limited evaluation of its impact. Aim: To measure the impact of dementia communication training (based on VERA) plus older adult unit (OAU) placement on students' ability to recognise opportunities for person centred (PC) communication compared to OAU placement alone. Method: A control pre-post-study design was used. Dementia communication training plus follow-up during OAU placement was delivered to 51 students (5 OAU, two hospitals) while 66 students (7 OAUs, five hospitals) acted as controls. The primary outcome was students' ability to recognise PC communication assessed using case vignettes. Data were collected using electronic survey and focus group interviews. Data analysis used independent non-parametric Mann-Whitney U test and thematic analysis. Results: In total 52 students (response rate 40%) completed surveys at the end of placements (38 intervention, 14 control group students). In the intervention group, participants were significantly more likely to identify PC responses with a mean score of 10.5 (SD 3.0) compared with 7.5 (SD 3.0) in the control group ( p = 0.006). In focus group interviews ( n = 19 students), the main themes were connecting with patients, VERA in practice, communication challenges, and learning environment. VERA was described as a flexible approach that added to participants' communication toolkit. The learning environment, complexity of patients and organisational resources were important contextual factors. Conclusion: The VERA framework has potential as a foundation level dementia communication training intervention, but it requires more rigorous testing. Nursing can lead the way in developing and embedding evidence-based, interdisciplinary dementia communication training in preregistration curricula. Highlights: The dementia training based on the VERA framework was well received by students and feasible to deliver. The training significantly increased students' ability to recognise person-centred responses compared to the control group. The VERA intervention worked by increasing students' confidence and adding to their communication toolkit. The learning environment and lack oforganisational resources impactedon students' experiences of dementia care.